086. Combination of Mustarde Flap and Paramedian Forehead Flap in Nasal Non-Melanoma Basal Cell Carcinoma: A Case Report - Pranatalenta, Eka; Setiawan, I Gede Budhi (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p086, 2024)
Background : Basal cell carcinoma (BCC) is a non-melanocytic skin cancer, specifically an epithelial tumor originating from basal cells. The National Comprehensive Cancer Network (NCCN) states that the primary goal of treating BCC is to eliminate the tumor to prevent its locally invasive and damaging characteristics while preserving function and aesthetic appearance as much as possible. This case report details a patient who experienced a defect on the nose due to surgery. Case : A sixty-year-old male patient came to our center with a lump on the right side of his nose, which had developed about 1.5 years prior to his admission. Over the last year, the initially small lump progressively enlarged in both size and depth, becoming ulcerated and necrotic. Clinical examination showed multiple lumps on the right side of the nose with a necrotic edge and ulceration, but without any signs of bleeding. Laboratory tests showed normal results. Conclusion : Facial defects caused by BCC may require various reconstruction approaches depending on the size and location. A combination of skin flap techniques, such as the paramedian forehead flap and Mustardé flap, shows outstanding functional and cosmetic outcomes.